Vielfältig verflochten: Interdisziplinäre Beiträge zur Tier-Mensch-Relationalität - Forschungsschwerpunkt »Tier – Mensch – G (transcript, 2017)
Animal-human relationships are diverse and currently a hot topic of discussion. The contributions in this interdisciplinary volume focus on the concept of relationality, showing that interactive relationship structures can be found, for example, in medieval allegorical readings of nature, and in the change in breeding objectives for prize cattle. In both the reintroduction of animals into native habitats and animal rights activism, symmetrical relationships and direct interactions are pursued. Through an examination of animal slaughter as an artistic activity and the constitution of insects for a taxonomic classification in the 18th century, the mutual conditioning of animals and humans is demonstrated.